2022
DOI: 10.3389/fphar.2022.931670
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptomics and metabolomics reveals the molecular mechanisms underlying the effect of nafamostat mesylate on rhabdomyolysis-induced acute kidney injury

Abstract: Objective: To investigate the role and mechanisms of action of nafamostat mesylate (NM) in rhabdomyolysis-induced acute kidney injury (RIAKI).Methods: RIAKI rats were assigned into control group (CN), RIAKI group (RM), and NM intervention group (NM). Inflammatory cytokines and proenkephalin a 119–159 (PENKID) were assessed. Cell apoptosis and glutathione peroxidase-4 (GPX4) were detected using TUNEL assay and immunohistochemical staining. Mitochondrial membrane potential (MMP) was detected by JC-1 dye. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“… 78 It was found that nalmestat mesylate could inhibit the development of RM-AKI by mediating ferroptosis pathways such as glutathione metabolism and ferritin metabolism, as well as regulating the inflammatory response and associated expression of key differentially expressed genes, and it was suggested that nalmestat mesylate could be a potential target drug for the targeted treatment of RM-AKI. 79 …”
Section: Ferroptosis and Rhabdomyolysis Syndrome-induced Akimentioning
confidence: 99%
“… 78 It was found that nalmestat mesylate could inhibit the development of RM-AKI by mediating ferroptosis pathways such as glutathione metabolism and ferritin metabolism, as well as regulating the inflammatory response and associated expression of key differentially expressed genes, and it was suggested that nalmestat mesylate could be a potential target drug for the targeted treatment of RM-AKI. 79 …”
Section: Ferroptosis and Rhabdomyolysis Syndrome-induced Akimentioning
confidence: 99%
“…Data integration often involves aligning data with corresponding Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Guo et al [22] successfully utilized combined transcriptomic and metabolomic analyses to understand the molecular mechanisms underlying the effects of drugs on acute kidney injury. Overall, integrating multiple omics data can help identify previously unrecognized interrelationships between different biological or molecular pathways.…”
Section: Introductionmentioning
confidence: 99%